Cordelia Underwood, or, The marvelous beginnings of the Moosepath League - Reid, Van. (New York : Penguin Books, 1999)
In 1896, after Cordelia Underwood inherits land from her uncle and Tobias Walton, unusual incidents begin to happen.
"A New York Times notable book"--Cover.
Includes a preview of Mollie Peer, the second Moosepath League novel, and a reader's guide to the Moosepath League books.
Maine author. Van Reid lives in Edgecomb, Me.
Keywords: Kidd, William, -- -1701.; Moosepath League (Imaginary organization) -- Fiction; City and town life -- Maine -- Portland -- Fiction; Women landowners -- Maine -- Fiction; Young women -- Maine -- Fiction; Authors, American -- Maine; Historical fiction; Treasure troves -- Fiction; Maine -- Fiction; Portland (Me.) -- Fiction; Adventure fiction